MEDIATING MENTAL ILLNESS: DIGITAL LIFEWORLDS, PLATFORMS AND ALGORITHMS - Hendry, Natalie Ann; Wan, Evelyn; Flore, Jacinthe; McCosker, Anthony; Kamstra, Peter; Farmer, Jane (AoIR Selected Papers of Internet Research, 2020)
How is mental illness conceptualised, designed, experienced or produced by digital life? This panel explores how digital technologies and media are transforming the performance, recognition, and experience of mental illness. We bring together different methodological and theoretical contributions towards an interdisciplinary study of mental illness and digital life. Our first two papers analyse specifically chatbots and ingestible sensors that are used for diagnosis, monitoring, and treatment of mental illness in their entanglements with private companies, state policy, and university lab experimentations. Our first paper frames the emerging field of computational psychiatry as a biopolitical form of governance of mental illness through algorithmic and digital means, and analyses the logic of control through the example of a cognitive-behavioural therapy chatbot for depression and anxiety. The second paper turns to the body as a site of intervention for the treatment of psychiatric diagnoses and explores how we can think through the assemblages of digital technology, embodiment and moods associated with mental illness. Understanding online forums as potentially “enabling places,” the third paper discusses the relationships between space and location, and social experiences of mental ill-health on online forums posted by forum users living in remote areas in Australia. Our final paper considers the absence of these “enabling places” as digital platforms disafford familial or relational experiences of mental illness, and design out families where a parent or adult carer lives with mental illness.